The impact of user fees on health services utilization and infectious disease diagnoses in Neno District, Malawi: a longitudinal, quasi-experimental study - S. I. Watson; E. B. Wroe; E. L. Dunbar; J. Mukherjee; S. B. Squire; L. Nazimera; L. Dullie; R. J. Lilford (BMC, 2016)
Abstract Background User fees have generally fallen out of favor across Africa, and they have been associated with reductions in access to healthcare. We examined the effects of the introduction and removal of user fees on outpatient attendances and new diagnoses of HIV, malaria, and tuberculosis in Neno District, Malawi where user fees were re-instated at three of 13 health centres in 2013 and subsequently removed at one of these in 2015. Methods We conducted two analyses. Firstly, an unadjusted comparison of outpatient visits and new diagnoses over three periods between July 2012 and October 2015: during the period with no user fees, at the re-introduction of user fees at four centres, and after the removal of user fees at one centre. Secondly, we estimated a linear model of the effect of user fees on the outcome of interest that controlled for unobserved health centre effects, monthly effects, and a linear time trend. Results The introduction of user fees was associated with a change in total attendances of −68 % [95 % CI: −89 %, −12 %], similar reductions were observed for new malaria and HIV diagnoses. The removal of user fees was associated with an increase in total attendances of 352 % [213 %, 554 %] with similar increases for malaria diagnoses. The results were not sensitive to control group or model specification. Conclusions User fees for outpatient healthcare services present a barrier to patients accessing healthcare and reduce detection of serious infectious diseases.